Why we remember ebook Unlocking memory's power to hold on to what matters. - Ranganath, Charan (2024)
NEW YORK TIMES BESTSELLER • LOS ANGELES TIMES BESTSELLER • Memory is far more than a record of the past. In this groundbreaking tour of the mind and brain, one of the world’s top memory researchers reveals the powerful role memory plays in nearly every aspect of our lives, from recalling faces and names, to learning, decision-making, trauma and healing. A BEST SCIENCE BOOK OF THE YEAR: Financial Times, Smithsonian Magazine, The Telegraph, Waterstones, The Times, Marie Claire, Greater Good Magazine, Bookshop.org " Why We Remember offers a radically new and engaging explanation of how and why we remember." —Dr. Matthew Walker, author of Why We Sleep "Prominent neuroscientist and Guggenheim Fellow Charan Ranganath guides us through the science of our memories with incredible insight and clear science. He combines fascinating tales of the peculiarities of memory with practical, actionable steps. Not only will every reader remember better afterward, they’ll also never forget this life-changing book.” —Siddhartha Mukherjee, Pulitzer Prize-winning author of The Emperor of Maladies and Gene A new understanding of memory is emerging from the latest scientific research. In Why We Remember , pioneering neuroscientist and psychologist Charan Ranganath radically reframes the way we think about the everyday act of remembering. Combining accessible language with cutting-edge research, he reveals the surprising ways our brains record the past and how we use that information to understand who we are in the present, and to imagine and plan for the future. Memory, Dr. Ranganath shows, is a highly transformative force that shapes how we experience the world in often invisible and sometimes destructive ways. Knowing this can help us with daily remembering tasks, like finding our keys, and with the challenge of memory loss as we age. What’s more, when we work with the brain’s ability to learn and reinterpret past events, we can heal trauma, shed our biases, learn faster, and grow in self-awareness. Including fascinating studies and examples from pop culture, and drawing on Ranganath’s life as a scientist, father, and child of immigrants, Why We Remember is a captivating read that unveils the hidden role memory plays throughout our lives. When we understand its power— and its quirks—we can cut through the clutter and remember the things we want to remember. We can make freer choices and plan a happier future.